[OP.8E.04] ASSOCIATION BETWEEN DIETARY CHLORIDE, BLOOD PRESSURE AND HEART RATE – A RANDOMISED CROSS-OVER STUDY. (September 2016) - McCallum, L.; Boal, A.H.; Padmanabhan, S.
Abstract : Objective: Whilst there is general consensus that increased sodium chloride (NaCl) intake increases blood pressure (BP) and heart rate (HR) through effects on volume and sympathetic activity, there is uncertainty about the relative influence of sodium and chloride on these parameters. Evidence from interventional studies indicate that the BP response to salt is derived from chloride rather than sodium. Epidemiological studies indicate that low serum chloride, not sodium, is associated with higher mortality. Although food labelling/dietary recommendations specify NaCl or salt content, there is evidence that the sodium and chloride content are not equimolar. We hypothesise that cardiovascular response to different foods differ in relation to variation their sodium and chloride content. We conducted a randomised cross-over study of foods with similar sodium but differing chloride content. Figure. No caption available. Design and method: Six foods with different chloride:sodium ratios were tested in healthy volunteers randomised to two arms, each crossing-over three foods. Cake/bread arm: cake (salt intake by label:0.98 g; food electrolyte ratio: low chloride:sodium), rye (salt:0.97 g; equal sodium:chloride), white (salt:1 g; high chloride:sodium); crisp arm: salted (salt:1 g; high chloride:sodium), unsalted (salt:0 g; high chloride:sodium) and tortilla (salt:1 g; neutral chloride:sodium). BP and HR were measured at 15-minute intervals using an ambulatory blood pressure monitor, for three hours following food consumption. Comparisons made for AUC using paired t-tests. Results: 39 participants (cake/bread 20, crisps 19); 59% female; mean age (years) 31. Mean SBP (mmHg): 113.7 (salted), 115.3 (unsalted), 114.4 (tortilla), 114.3 (cake), 112.8 (white) and 112.5 (rye). There was no significant difference between groups for SBP or DBP. In the cake/bread arm, the HR for cake was significantly higher than rye bread (paired difference 29.95; p = 0.046) while in the crisps arm, the HR for salted and unsalted crisps were lower than tortilla (paired differences −42.15 & −37.85; p = 0.012 & 0.006). Conclusions: There was a strong relationship between HR and chloride level which aligns well with chloride physiology and epidemiologic evidence and implicates known influence of chloride on sympathetic system or cardiac conduction system. Chloride may be an independent player in HR regulation and further study is required, which may have clinical and public health implications.